Semantic Classification of the Proverbs of the Tatar Language with Numeral-Component "Бер" (One) - Valieva, Julia Ju.; Nigmatullina, Alsu M. (Journal of History Culture and Art Research, 2017)
This paper considers the proverbs of the Tatar language with a numeral component «бер» / “ber” (one). Reasoning from the meaning of the numerals used in the introduced phraseological units, conditional semantic groups have been formed. In the course of the analysis, we have identified two large semantic groups: “Greed” and “Character traits”, and the subgroups within these two large groups. As a result of the analysis, it has been found that the combination with the noun «бертиен» (one kopeck) is used together with the words having a negative connotation. In most of the examples given, the character traits are rendered in combination of the numerals with the noun («бертиен» (one penny), «беркашыксу» (a spoonful of water), and the negative connotation of the proverbs is conveyed by means of the words with negative meanings such as «сусалмас» (someone will not give water); «каратиргә төшеп сатулашу» (bargain to all of a sweat), etc. The results of this work can be used in further studies of the semantics of numerals used in proverbial sayings; in formulating a classification of phraseological units with a numeral component; for comparative-contrastive analysis of the translations of set expressions from one language to another.